Revitalization of Disaster Theological Characteristics in the Perspective of the Quran - Ubaidillah, Ubaidillah (Madania: Jurnal Kajian Keislaman, 2021)
The risks and impacts of natural disasters and humanity have twisted people perceptions of sin and mistakes that are not entirely true. There are orientation, purpose, and the distinction between natural disasters and disasters in the concept of disasters in the Quran. The ideological doctrine of disasters such as ‘iqâb, fitnah, mushîbah, or ‘azâb in the Quran is made unilateral claim without considering the geographical and disaster aspect. The disasters are now evolving into implicative social phenomena rather than cause and effect. This research aims to provide a more balanced explanation in describing the concept of disaster in the Quran by using disaster and paradigm of social change theory. By employing the thematic interpretation method with a structural semantic approach, it is expected to give a new perspective on the concept of disaster. The results are: the first, conceptually natural disasters have restorative, regenerative and humanistic goals. The second, the disaster phenomena have the spirituality dimension to restore common sense and human ethics. The third, the disasters have various forms and characteristics as a consequence of human deeds more as grace than wrath. Therefore, the disaster orientation is not considered as hatred but as God's grace or affection for human. Resiko dan dampak bencana alam dan kemanusiaan telah membentuk persepsi masyarakat tentang dosa dan kesalahan yang tidak sepenuhnya benar. Terdapat pembeda antara bencana alam dan bencana serta orientasi dan tujuan dalam konsep kebencanaan di dalam Alquran. Masalah yang muncul kemudin adalah doktrin teologis bencana seperti iqab, fitnah, musibah, atau azab  dalam Alquran dijadikan klaim sepihak tanpa mempertimbangkan aspek geografis dan kebencanaan. Bahkan bencana kini berkembang menjadi fenomena sosial yang bersifat implikatif dari sekedar sebab akibat. Penelitian ini bertujuan untuk memberikan penjelasan yang lebih berimbang dalam menjelaskan konsep bencana dalam Alquran dengan menggunakan teori bencana dan paradigma perubahan sosial. Melaui metode tafsir tematik dengan pendekatan semantik struktural diharapkan dapat memberikan perspektif baru tentang konsep kebencanaan. Hasilnya, pertama, bencana alam secara konseptual memiliki tujuan restoratif, regeneratif dan humanitis. Kedua peristiwa bencana memiliki dimensi spiritualitas untuk mengembalikan akal sehat dan budi pekerti manusia. Ketiga, bencana memiliki beragam bentuk dan karakteristik sebagai konsekuensi perbuatan manusia lebih sebagai rahmat ketimbang murka. Dengan demikian, orientasi bencana bukan sebagai kebencian tetapi lebih sebagai rahmat atau kasih sayang Tuhan kepada manusia.